Virtual design software for mechanical system dynamics using transfer matrix method of multibody system and its application. (3rd September 2015) - Yang, Hai-gen; Rui, Xiao-ting; Zhan, Zhi-huan; Zhang, Jian-su; Gu, Jun-jie; He, Bin
The complex mechanical systems such as high-speed trains, multiple launch rocket system, self-propelled artillery, and industrial robots are becoming increasingly larger in scale and more complicated in structure. Designing these products often requires complex model design, multibody system dynamics calculation, and analysis of large amounts of data repeatedly. In recent 20 years, the transfer matrix method of multibody system has been widely applied in engineering fields and welcomed at home and in abroad for the following features: without global dynamic equations of the system, low orders of involved system matrices, high computational efficiency, and high programming. In order to realize the rapid and visual simulation for complex mechanical system virtual design using transfer matrix method of multibody system, a virtual design software named MSTMMSim is designed and implemented. In the MSTMMSim, the transfer matrix method of multibody system is used as the solver for dynamic modeling and calculation; the Open CASCADE is used for solid geometry modeling. Various auxiliary analytical tools such as curve plot and animation display are provided in the post-processor to analyze and process the simulation results. Two numerical examples are given to verify the validity and accuracy of the software, and a multiple launch rocket system engineering example is given at the end of this article to show that the software provides a powerful platform for complex mechanical systems simulation and virtual design.